Hesitation strategies engaged by foreign language (FL) learners during an interview - Sadatmir, Seyedehsima; Maryamabadi, Narjes Karimi (Universiti Putra Malaysia Press, 2017)
Hesitations are pauses with different lengths, which are not generally left unfilled. They occur when the speaker is at a loss for words or engages in cognitive or verbal planning. Hesitation strategies belong to the larger class of ‘disfluencies’ or ‘self-repairs’. The objectives of this article are, firstly, to identify the hesitation strategies used by FL (Foreign Language) learners when participating in an interview and, secondly, to identify the distribution of hesitation occurrences during a discourse. This study presents an investigation of hesitation strategies among fifteen international students from one of the public universities in Malaysia. Video and audio recording were used for all participants during the interview. Two standard interviews were prepared for each participant. The interviewer asked a few questions about two specific topics from each participant. Concentrating on hesitations, DF (Disfluency) and pauses, and idiosyncratic fillers, the interviews were transcribed and analysed qualitatively. The video recordings were also coded and analysed according to non-verbal/paralinguistic features, including different body gestures. The results indicated the disability to speak fluently was endemic among the FL students even though they possessed linguistic abilities. Consequently, they need to be taught to apply effective oral skills, including appropriate hesitation strategies, to improve their ability in fluent speech production.